The Role of Social, Spiritual, and Financial Capital on the Entrepreneurial Interest of Sharia Economics Students: A Qualitative Approach - Ardika Putri, Oktaria (Pascasarjana, Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to explore the roles of social, spiritual, and financial capital in shaping the entrepreneurial interest of Islamic Economics students. Using a descriptive qualitative approach and a case study method, the study involved 15 students from three Islamic higher education institutions in Indonesia, selected through purposive sampling. Data were collected through in-depth interviews and participatory observation, and analyzed using thematic techniques. The findings reveal that social capital—including networks, trust, and social norms—plays a significant role in enhancing students’ entrepreneurial confidence. Spiritual capital strengthens internal motivation and Islamic value orientation in business practices, while financial capital supports readiness by improving financial literacy and access to sharia-compliant financing. The integration of these three forms of capital creates a holistic and sustainable entrepreneurial ecosystem among students. The findings recommend strengthening value-based entrepreneurship programs, skills development, and access to Islamic financial resources within Islamic higher education institutions.